Mater, Virgo et Regina : Frei Nicolau Dias e o Rosário da Virgem Maria (Portugal - 1573) - Cordeiro, André Rocha (2017)
This study is focused on the understanding of the Marian representations as well as the analysis of the promotional speech in devotion to the Rosary of the Virgin Mary in the book Livro do Rosário de Nossa Senhora (Book of the Rosary of Hail Mary), written by Fray Nicolau Dias in 1573.The dissertation brings contributing considerations to the History of Religion studies, mainly in regard to Catholicism in the 16th century in Portugal, using the social place and practical formality authorized language concepts (CERTEAU, 1982), as well as appropriation and representation ( CHARTIER 1990; 1991), and allowed language (BOURDIEU, 2007). Our starting point was the author?s biography as a Dominican Master in Theology, in Portugal, likewise his articulations of the historical context and the institutions in which he was a member of, such as the Catholic Church and the Order of Preachers. Subsequently, our aim is the understanding of Virgin Mary?s portray in the book as a comparison to the Catholic Church established concepts worshiped by the devotees: Mother, the Virgin Queen, Mediatrix and Advocate. Lastly, it analyzes the elements used by Dias to promote devotion to the Virgin Mary and the Rosary, and also highlights the elaboration of the speech in defense of Order of Preachers related to Marian devotion